Millicent Garrett Fawcett (UCL Press, 2022)
‘Courage calls to courage everywhere’ is the best-known phrase associated with Millicent Garrett Fawcett (1847-1929), the leading UK suffragist and campaigner of the late 19th and early 20th centuries. But what is the source of her quote, and what is its context? This book reproduces Fawcett’s essential speeches, pamphlets and newspaper columns to tell the story of her dynamic contribution to public life. Thirty-five texts and 22 images are contextualised and linked to contemporary news coverage as well as to historical and literary references. These speeches, articles, artworks and photographs cover both the advances and the defeats in the campaign for women’s votes. They also demonstrate a variety of the topics and causes Fawcett pursued: the provision of education for women; feminist history; a love of literature (and Fawcett’s own attempt at fiction); purity and temperance; the campaign against employment of children; the British Army’s approach to the South African War; the Unionist cause against Home Rule for Ireland; and the role of suffrage organisations during the Great War. Here is a rich, intertextual web of literary works, preferred reading material, organisations, contacts, friends, and sometimes enemies, that reveals Fawcett the individual throughout 61 years of campaigning. The first scholarly appraisal of Fawcett in over 30 years, this is essential reading for those wishing to understand the varied political, social and cultural contributions of Dame Millicent Garrett Fawcett. Praise for Millicent Garrett Fawcett: Selected writings 'Millicent Fawcett’s influence in the suffrage movement is often overlooked in favour of the more radical suffragette Emmeline Pankhurst. Millicent was hugely important, concentrating on non violent rational persuasion. This book explains the work of this dogged suffragist.' Dame Jenni Murray - former president Fawcett Society 'Millicent Garrett Fawcett: Selected writings invites the reader to delve into the life and passions of this great suffragist leader. Millicent Fawcett paved the way for women to take their place in public life, that’s why I’m so proud that in 2018, her sculpture was unveiled in London, becoming Parliament Square’s first-ever statue of a woman. The statue depicts Millicent holding a banner bearing the powerful quote, “Courage Calls to Courage Everywhere”. This book explores important aspects of the rich and too-often untold history of women’s rights, including the origins of that inspirational quote.' Sadiq Khan, Mayor of London 'This is a vital collection of the vital speeches of a vital person. You need to read this to understand the history of Millicent Fawcett and if you don’t understand the history of Millicent Fawcett you don’t understand one of the most important developments in modern civilisation.' Lord Daniel Finkelstein 'Millicent Fawcett is one of the pivotal voices in UK political history. Her work paved the way for every woman who has ever taken her place in a parliament anywhere on these islands. When any of us talk about standing on the shoulders of giants, Millicent Fawcett was that giant of female empowerment.' Baroness Ruth Davidson 'Millicent Fawcett was one of the most influential figures of her age, yet history has tended to overlook her. Extraordinarily astute and forward-thinking, she inspired women to change their world by giving them a political voice, and the confidence to use it. Thanks to this collection, which is both scholarly and accessible, we can now hear her own voice as never before. She continues to inspire us to speak out on behalf of women's progress everywhere.' Jane Robinson, Senior Associate, Somerville College, Oxford; author of Ladies Can't Climb Ladders: The Pioneering Adventures of the First Professional Women